Galen's Treatise 'Thrasybulus' and the dispute between 'Paidotribes' and Gymnastes' - Nieto Ibáñez, Jesús María (Nikephoros: Zeitschrift für Sport und Kultur im Altertum, 2003)
The revival of Greek sport in the second century AD coincides with the medical and philosophical critique of Galen against professional athletics, which has nega- tive effects on health and ethical and moral valúes. The treatise Thrasybulus sive utrum medicinae sit an gymnasticae hygieine is a doctrinal justification of the tech- nique of the gymnastes in contrast with that of the paidotribes.